Hybridized trajectory generation and many-objectives optimization for multi-agent quadrotor UAVs - Tharumanathan, Premeela (2018)
This research generates a large collection of optimized trajectories for multi-agent quadrotors. The hybridized algorithm extracts trajectories with various trade-off for all agents without discrimination. This allows the resources of all agents to contribute towards the completion of a task.